2021
DOI: 10.1101/2021.10.03.21264490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Post COVID-19 Health Problems and its Determinants in North India: A descriptive cross section study

Abstract: With millions of people getting affected with COVID-19 pandemic caused by a novel severe acute respiratory syndrome corona virus 2 (SARS-CoV-2), people living with post COVID-19 Symptoms (PCS) are expected to rise in the future. The present study aimed at assessing PCS comprehensively and its associated factors among COVID-19 recovered adult population in north India. Methods: In a tertiary health centre at Delhi, an online based cross-sectional study was conducted using a semi-structured questionnaire, develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 28 publications
3
28
0
2
Order By: Relevance
“…The PCS found to be most prevalent in our study have also been reported by previous studies done in different parts of the world (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), although the relative distribution varied among cohorts, as did the demographic and clinical associations. The most extensive and long physical follow-up study, done in Wuhan, China, reported fatigue and muscle weakness (63%) and sleep difficulties (26%) to be the most prevalent PCS at a median of 186 days since symptom onset (N=1655) (9).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The PCS found to be most prevalent in our study have also been reported by previous studies done in different parts of the world (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), although the relative distribution varied among cohorts, as did the demographic and clinical associations. The most extensive and long physical follow-up study, done in Wuhan, China, reported fatigue and muscle weakness (63%) and sleep difficulties (26%) to be the most prevalent PCS at a median of 186 days since symptom onset (N=1655) (9).…”
Section: Discussionsupporting
confidence: 90%
“…A north Indian single hospital study collected data from a younger cohort of patients (N=773, median age 34 years) and reported the prevalence of PCS (again most common being fatigue) to be 12.8% at 3 months since diagnosis. This study also reported PCS to be more prevalent in females (17).…”
Section: Discussionsupporting
confidence: 70%
“…Senjam et al [ 14 ] conducted a cross-sectional study aimed to examine a total of 773 participants with confirmed COVID-19 infection by asking them to complete a survey over a 6-week period. Of those participants, 407 were unvaccinated, 173 were partially vaccinated, and 193 were fully vaccinated.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, by preventing infection with SARS-CoV-2 (Level 1); secondly, by reducing the severity of the disease in vaccinated but infected individuals (Level 2); and finally, vaccination may benefit people who already have long COVID (Level 3). However, recent observational studies provide contradictory results and contain methodological flaws which preclude firm conclusions on level 2 and 3 vaccine impact (6, 7).…”
Section: Introductionmentioning
confidence: 99%